THE IMPACT OF MARKET ACCESS ON INPUT USE AND AGRICULTURAL PRODUCTIVITY AMONG CEREAL CROP FARMERS IN NIGER STATE, NIGERIA - OJO, M.A.; DIYE , M.; COKER, A.A.A; OJO , A.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
The study examined the effect of market access on input used and agricultural productivity among cereal crop farmers in Niger State, Nigeria. Data used for this study were collected from primary sources using multi-stage sampling technique with structured questionnaire administered to 250 randomly selected cereal crop farmers in Niger State. Descriptive statistics, total factor productivity (TFP) and three stages least square (3SLS) regression were used to analyse the data collected. The results revealed that cereal crop farmer’s productivity increased with easy market access to inputs across farm size groups in the study area. The study further revealed market access had positive and significant effect on fertilizer; agrochemical and high yielding seed used at 5% and 1% probability levels respectively. The study revealed that decrease in time to market led to 2% increase in cereal crop farmers’ productivity in the study area. The productivity (Model I) had chi square value of 25.01, which is statistically significant at 1% probability level. The fertilizer used (Model II), agrochemical used (Model III) and high yielding seed (Model IV) had chi-square values of 453.19, 257.26 and 8.57 respectively and these values were all statistically significant at 1% probability level. This implies that all the explanatory variables included in each of these models jointly explained variations in their dependent variables in the study area. The study also revealed that the major constraints faced by cereal crop farmers were diseases, pests attack, and inadequate credit facilities in the study area.  Based on the above findings, the study recommends that government should provide enabling environment to support private sector operatives of the agro-inputs industry, with the view to providing adequate farm input to farmers in the study area.